CLIMATE CHANGE: FUNDAMENTALS AND REGULATION OVERVIEW IN INDONESIA - Desy Maritha (Puslatbang KHAN, 2020)
From its trending phenomenon, climate change adaptation and mitigation becomes mainly discussed in global discourse, including from the fundamental and law perspective. This article aims to elaborate decriptively the fundamentals concept of Climate Change Adaptation and Mitigation. First section, the paper describes the fundamental of climate change concept. Second section, explains the previous researches regarding climate change adaptation and mitigation, and lastly elaborates the regulatory framework and list of the regulation enforcement in Indonesia. In addition, it also provides the historical overview of first enforcement of the Law, Presidential decree, the instructions of Ministry of Environment and Forestry. The History began since the ratification of law products from United Nations Framework Convention on Climate Change (UNFCC) in 1992, Kyoto Protocol, Bali Roadmap and several regulations regarding the Climate change management and control.